Feeding and Vaccination techniques to improve the health and production of Beef Cattle - Annisa, Istiqama Maulidina (Journal of Agro Complex Development Society, 2024)
Beef cattle are one of the important sources of animal protein for the people of Indonesia. However, beef cattle productivity is still low compared to other countries. One factor affecting beef cattle's health and production is feeding and vaccination techniques. This article discusses feeding and vaccination techniques that can improve the health and production of beef cattle. These techniques include the selection of feed type, frequency of feeding, quantity of feed, feed quality, mineral supplements, routine vaccination, and disease management. Applying these techniques is expected to improve cattle growth, reproduction, health and quality.